Color and design - DeLong, Marilyn Revell, 1939-; Martinson, Barbara (Berg, 2012)
"From products we use to clothes we wear, and spaces we inhabit, we rely on color to provide visual appeal, data codes and meaning. Color and Design addresses how we understand and experience color, and through specific examples explores how color is used in a spectrum of design-based disciplines including apparel design, graphic design, interior design, and product design. Through highly engaging contributions from a wide range of international scholars and practitioners, the book explores color as an individual and cultural phenomenon, as a pragmatic device for communication, and as a valuable marketing tool. Color and Design provides a comprehensive overview for scholars and an accessible text for students on a range of courses within design, fashion, cultural studies, anthropology, sociology and visual and material culture. Its exploration of color in marketing as well as design makes this book an invaluable resource for professional designers. It will also allow practitioners to understand how and why color is so extensively varied and offers such enormous potential to communicate"-- Resumé vydavatele